Extending of vase life of Narcissus tazetta by AVG and antimicrobial agents - Gun, S (Journal of Postharvest Technology, 2020)
The study was carried out to determine the effect of Aminoethoxyvinylglycine (AVG) (10 and 5 ppm), salicylic acid (SA) (100 ppm) and citric acid (CA) (100 ppm) applications on vase life, relative fresh weight, daily water uptake and total water uptake (100 ppm) of narcissus (Narcissus tazetta L.) cut flower. In the research, the longest vase life was obtained from 5 ppm AVG application with 12 days. In addition, 10 ppm AVG and 100 ppm citric acid applications significantly increased vase life compared to control. Fresh weight, daily water uptake and total water uptake were significantly higher in AVG (10 and 5 ppm) applications compared to other applications. As a result, it was determined that AVG has a positive effect on vase life of Narcissus tazetta flower.